Ankyrin repeat domain 1 regulates innate immune responses against herpes simplex virus 1: A potential role in eczema herpeticum - Bin, Lianghua; Li, Xiaozhao; Richers, Brittany; Streib, Joanne E.; Hu, Jack W.; Taylor, Patricia; Leung, Donald Y.M. (Journal of allergy and clinical immunology, 2018)
Atopic dermatitis (AD) is a common inflammatory skin disease. A subset of patients with AD are susceptible to disseminated herpes simplex virus (HSV) infection, a complication termed eczema herpeticum (ADEH+). The immune mechanisms causing ADEH+ remain elusive. Using RNA sequencing, we recently found that ankyrin repeat domain 1 (ANKRD1) was significantly induced in human PBMCs upon HSV-1 stimulation, and its induction in patients with ADEH+ was significantly reduced compared with that seen in AD patients without a history of eczema herpeticum (ADEH−). We sought to validate ANKRD1 gene expression in nonatopic (NA) subjects, patients with ADEH−, and patients with ADEH+ and to delineate the biological function of ANKRD1 and the signaling pathway or pathways involved. Purification of human PBMCs, monocytes, B cells, dendritic cells, T cells, and natural killer cells; RNA extraction and quantitative RT-PCR; small interfering RNA technique; co-immunoprecipitation; and Western blot assays were used. ANKRD1 expression was significantly reduced in PBMCs from patients with ADEH+ after HSV-1 stimulation compared with PBMCs from patients with ADEH−. We found that the induction of ANKRD1 by HSV-1 and multiple pattern recognition receptor agonists are mediated by inflammatory cytokines. Silencing ANKRD1 gene expression in antigen-presenting cells led to increased viral load and reduced IFNB1 and IL29 production. Using co-immunoprecipitation methods, we demonstrated that ANKRD1 formed protein complexes with interferon regulatory factor (IRF) 3 and IRF7, which are important transcription factors regulating signaling transduction of pattern recognition receptors. Overexpression of ANKRD1 enhanced the IRF3-mediated signaling pathways. ANKRD1 is involved in IRF3-mediated antiviral innate immune signaling pathways. Its reduced expression in patients with ADEH+ might contribute to the pathogenesis of ADEH+.